Global Warming : Impacts and Future Perspective - Raj Singh, Bharat; Raj Singh, Bharat (IntechOpen, 2012)
Global Warming has become perhaps the most complicated issue being faced by world leaders. Thus, it requires field of attention for many modern societies, power and energy engineers, academicians, researchers and stakeholders. The so-called consensus in the past century anthropogenically induced Global Warming, has recently been disputed by rising number of climate change panelists. Whatever the uncertainties of climate models are, mankind has to strive towards reduction in the amount of greenhouse gases emitted into the atmosphere in order to preserve natural resources and living organisms by introducing new advances on alternative fuels and other related technologies. This book presents the state-of-the-science fundamentals on the origin of Global Warming and other related technologies that can be implemented to reduce human impact as well as to present novel policies that world leader should adopt. In this book, chapters received from various authors are placed in three sub- sections in a sequential and easy manner so as to strive an appropriate balance between breadth and depth of coverage of various topics.
English
Keywords: Climate change; Climate change